CONSOLIDATED FINANCIAL STATEMENT FOR NIGERIA MULTINATIONAL CORPORATIONS: CHALLENGES AND BEST PRACTICE - Ogiriki, Tonye PhD, Monron Ezekiel Lawrence (International Journal of Global Economic Light, 2023)
This study is an overview on consolidated financial statements for Nigerian corporations, focusing on the challenges and best practices involved. The study adopts the Parent Company Extension Theory, which emphasizes the need to present combined financial reports that reflect the holding firm’s role as an extension of its subsidiaries. The research examines the challenges faced by Nigerian multinational corporations (MNCs), particularly in relation to diverse accounting standards and the acquisition of timely and accurate financial information from subsidiaries. The case study of MTN Group, a multinational telecommunications company operating in Nigeria, highlights specific challenges such as the complexity of the local regulatory environment and the need to comply with tax laws and regulations. To address these challenges, best practices are recommended, including compliance with local laws, engaging with regulators, establishing robust internal controls, investing in talent development, adopting common accounting policies, and continuous monitoring and adaptation. The study draws on empirical evidence from similar research conducted on multinational enterprises in various regions, providing insights into the challenges and solutions in preparing consolidated financial reports. The findings underscore the significance of accurate and transparent financial reporting for MNCs and emphasize the importance of standardization, effective communication, and risk management strategies. By implementing the recommended best practices, multinational corporations in Nigeria can enhance the accuracy, transparency, and reliability of their consolidated financial statements.